High-impact athletics after knee articular cartilage repair - Mithoefer, K.; Williams, R. J.; Warren, R. F.; Wickiewicz, T. L.; Marx, R. G. (The American Journal of Sports Medicine, 2006)
Knee articular cartilage injuries in athletes present a therapeutic challenge and have been identified as an important cause of permanent disability because of the high mechanical joint stresses in athletes.